2019
DOI: 10.1111/are.14374
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to feed restriction and starvation in juvenile Siberian sturgeon Acipenser baerii (Brandt, 1869): Effects on growth, body composition and blood plasma metabolites

Abstract: An 8-week study was applied to evaluate the effects of feed restriction and starvation on growth, proximate composition, haematological and biochemical factors in juvenile Siberian sturgeon Acipenser baerii with an average weight of 54 ± 0.6 g. Fish were randomly divided into nine indoor tanks (1,050 L volume) with 30 fish per tank in a flow-through system at 18 ± 0.4°C. Three feeding strategies were considered: I) fed at satiation (F), II) restricted feeding at the rate of 1% body weight per day (R) and III) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…sport fish species is not associated with reduced feeding during winter months. In Siberian Sturgeon Acipenser baeri that were grown at 18°C and subjected to one of three feeding regimens (satiation daily, 1% of body weight daily, or starved), fish that were not offered feed lost 21.6% of their body weight and had a reduced condition factor, but their survival rate was similar to that of their fed counterparts (Shirvan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sport fish species is not associated with reduced feeding during winter months. In Siberian Sturgeon Acipenser baeri that were grown at 18°C and subjected to one of three feeding regimens (satiation daily, 1% of body weight daily, or starved), fish that were not offered feed lost 21.6% of their body weight and had a reduced condition factor, but their survival rate was similar to that of their fed counterparts (Shirvan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…During periods of reduced winter feeding, whole-body moisture content often increases due to hydration of the organism's tissues (Ali et al 2003;Shirvan et al 2020), while muscle lipids and proteins are utilized if initial stores do not satisfy energy needs. However, in fish that are either starved or fed restricted rations, the whole-body protein composition changes less than whole-body lipid composition (Shearer 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This was in consistent with the findings in gibel carp (Carassius auratus gibelio var. CAS III) (51), hoplosternum littorale (Teleostei, callichthyidae) (52). Genes such as Hadha and Mgll were upregulated related to fatty acid hydrolysis, while other genes related to fatty acid synthesis such as ANGPTL4 and Ank1 were downregulated.…”
Section: Kidney Transcriptome In Response To Starvationmentioning
confidence: 99%
“…When fish are subjected to various stressors, RBC, unlike Hb and Ht, exhibits a variety of responses such as an increase, decrease, or no change ( Table S2 ). For instance, when fish is exposed to ammonia stress [ 25 ], pathogens [ 63 , 64 ], feed restriction [ 65 ], and silver nanoparticles [ 66 ], no change or increase in RBC in the stressed group than control was observed. Oxidative stress (which is a result of external and internal stressors) can damage the RBC membrane and impair its deformability [ 67 ].…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…Depending on their concentration, target cell, and the specific immune function studied, these elements have either an enhancing or suppressive effect on the immune system [ 71 ]. The increase of WBC under pollutions and herbicides [ 40 , 72 ], and silver nanoparticles [ 73 ], pathogens [ 63 ]; and no change with many other stressors [ 65 , 66 , 74 , 75 ] were observed. However, as with other haematological parameters, the majority of monitored studies revealed a decrease in WBC in the blood of stressed fish ( Table S2 ).…”
Section: White Blood Cellsmentioning
confidence: 99%